2014
DOI: 10.1007/s00109-014-1176-8
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A promotes ventricular remodeling after myocardial infarction

Abstract: Inflammatory responses play an important role in the pathogenesis of adverse ventricular remodeling after myocardial infarction (MI). We previously demonstrated that interleukin (IL)-17A plays a pathogenic role in myocardial ischemia/reperfusion injury and viral myocarditis. However, the role of IL-17A in post-MI remodeling and the related mechanisms have not been fully elucidated. Acute MI was induced by permanent ligation of the left anterior descending coronary artery in C57BL/6 mice. Repletion of IL-17A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…It has been reported that toll‐like receptor 4 mediates maladaptive left ventricular (LV) remodeling and impairs cardiac function after MI . Moreover, experimental studies from our laboratory demonstrated that interleukin (IL)–17A promotes ventricular remodeling after MI . These findings suggest that excessive immune‐mediated inflammatory reactions play a deleterious role in postinfarction ventricular remodeling.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has been reported that toll‐like receptor 4 mediates maladaptive left ventricular (LV) remodeling and impairs cardiac function after MI . Moreover, experimental studies from our laboratory demonstrated that interleukin (IL)–17A promotes ventricular remodeling after MI . These findings suggest that excessive immune‐mediated inflammatory reactions play a deleterious role in postinfarction ventricular remodeling.…”
Section: Introductionmentioning
confidence: 80%
“…4 Moreover, experimental studies from our laboratory demonstrated that interleukin (IL)-17A promotes ventricular remodeling after MI. 5 These findings suggest that excessive immune-mediated inflammatory reactions play a deleterious role in postinfarction ventricular remodeling. Paradoxically, immunosuppressive therapy with methylprednisolone resulted in increased catastrophic mortality due to cardiac rupture.…”
mentioning
confidence: 99%
“…Studies of the pro‐fibrotic effects of IL‐17 in the lung heart and liver have been undertaken. In the latter, IL‐17‐mediated liver fibrosis through hepatic stellate cell activation .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the protection of IL-17A -/mice in a mild IRI model, we could not see any effect on renal fibrosis over a period of 3 weeks in our study. Studies of the pro-fibrotic effects of IL-17 in the lung [28] heart [29] and liver [30] have been undertaken. In the latter, IL-17-mediated liver fibrosis through hepatic stellate cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of IL-17 in HF progression is unclear. Additionally, IL-17A has been shown to induce cardiac myocyte apoptosis in experimental HF [20], though anti-IL-17 therapies have not yet been studied in humans.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%